2023
DOI: 10.1111/pere.12513
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving in academia: Examining educator well‐being and burnout during prolonged stressors

Abstract: In the face of prolonged stress, care professionals, including educators, often experience higher rates of burnout and worsened mental well‐being. As school systems across the United States reconsidered their instructional practices in an effort to curtail the spread of COVID‐19, educators have had to navigate a new academic landscape hallmarked by change, stress, burnout, and hopefully resilience. Guided by the theory of resilience and relational load (TRRL), this national study of educators (N = 449; Mage = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that exposure to school-related stress was associated with decreased mental health and greater depression severity in educators 7 14 . Specifically, educators with greater perceived stress reported reduced emotional well-being 15 – 18 . In addition, educators who had to deal with greater disruptive behaviors, poorer student motivation, and increased workload reported higher distress and depressive symptoms 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure to school-related stress was associated with decreased mental health and greater depression severity in educators 7 14 . Specifically, educators with greater perceived stress reported reduced emotional well-being 15 – 18 . In addition, educators who had to deal with greater disruptive behaviors, poorer student motivation, and increased workload reported higher distress and depressive symptoms 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%